(untitled) (Journal of Al-farahidi’s Arts, 2026)
Objectives: This study examines the informative clause following the vocative (Jumlat al-Munāda Lahu al-Khabariyya) in the poetry of Nizar Qabbani, focusing on its syntactic structure and rhetorical significance. It is based on the hypothesis that, although these clauses appear to be declarative on the surface, their true function is performative (illocutionary). Thus, the research seeks to reveal how Qabbani employs the declarative structure to serve various expressive and emotive purposes that transcend mere reporting toward conveying emotional intensity and implicit requests. Methodology: The study adopts a descriptive-analytical approach by examining selected samples from Qabbani’s poetry and analyzing the informative clauses following the vocative within them, drawing on grammatical and rhetorical frameworks. The analysis focuses on the relationship between the syntactic form of the clause and its intended meaning in the poetic context